Effects of the COVID-19 Pandemic on Eating and Meat Consumption Habits of Turkish Adults - Güliz Haskaraca; Esra Bostanci; Yusuf Arslan (Turkish Journal of Agriculture: Food Science and Technology)
Animal originated proteins have great importance in meeting the daily protein need in a healthy and balanced diet due to their high protein content, amino acid pattern and good digestibility. Also, when included in a diet, they play an important role in the protection of individuals’ health and improving the life quality with their vitamin and mineral content. The aim of this study is to investigate the changes in meat and meat products consumption habits of people and whether they are concerned about reaching meat and meat products during the COVID-19 pandemic. For that purpose, a 24-question survey of 1000 people from several cities of Turkey was carried out. The majority of the participants stated that their consumption of red meat (77%), poultry meat (81%) and fish (66%) did not change due to the COVID-19 pandemic, while 10%, 8%, and 3% of the participants said their red meat, poultry meat and fish consumption increased, respectively. In addition, 13%, 11%, and 31% of the participants said there was a decrease in their red meat, poultry meat and fish consumption, respectively. The major reason for the decrease in red and white meat consumption was economic reasons, however, the reason for the decrease in consumption of fish was difficulties in reaching. During the COVID-19 pandemic, until the date that the survey was done, 12% of the participants had concerns about reaching meat and meat products. The main cause of their concern was being unemployed or losing their job after the COVID-19 pandemic.